Equipartition, inverse-Compton radiation, and PKS 0637-752 - Birkinshaw, M (2002)
The Chandra measurement of X-rays from the radio jet in PKS 0637-752 has implications for the source kinematics and energetics. This contribution discusses several possibilities for explaining the high X-ray output from the jet, emphasizing the impact on the assumption of equipartition between relativistic particles and fields in the jet plasma.